Advanced Virtual Human Modeling with Metahumans: Focus on Genderless Characters - Araujo, Victor Flávio de Andrade; Schmitt, Ana; Costa, Angelo B.; Pizzol, Natália Dal; Musse, Soraia R. (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI), 2024)
Virtual Humans (VHs) with high levels of anthropomorphism in visual appearance and behavior can enhance user experience in movies, games, and other interactive media. Users often seek human-like representations that include realistic movement, emotion, and gender, fostering a stronger sense of identification with VHs. Studies from Psychology have shown that people tend to evaluate characteristics of others within their own group differently, known as the in-group advantage. For example, women may be better at recognizing emotions in other women than in men. Researchers have also noted differences in feature recognition based on both the gender of the person and the gender of the perceiver, a phenomenon that also extends to VHs. Understanding how humans perceive VHs is crucial for improving user experience and representation in virtual environments. Gender is a key anthropomorphic characteristic in VHs, essential for representativeness, human identification, and user comfort. Typically, VHs assigned a specific gender exhibit stereotyped features such as movements, clothing, hairstyles, and colors, designed to be easily recognized by users. Insights into gender representation in VHs can guide the industry in modeling and animating VHs to achieve the desired impact. This tutorial introduces a methodology for modeling gender in VHs, from genderless virtual babies to genderless virtual adults, focusing on visual and behavioral aspects. Participants will learn how to create genderless VHs, enhancing gender representation and making virtual environments more inclusive for a diverse audience.